2019
DOI: 10.1177/0361684319828288
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Racial Microaggressions and Traumatic Stress Symptoms Among Black Women

Abstract: We investigated the relations between gendered racial microaggressions (i.e., subtle gendered racism), gendered racial socialization, and traumatic stress symptoms among Black women. We hypothesized that gendered racial microaggressions would be significantly associated with traumatic stress symptoms and that gendered racial socialization would moderate the relations between gendered racial microaggressions and traumatic stress symptoms. Participants were 226 Black women from across the United States who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 83 publications
5
102
2
Order By: Relevance
“…Based on the current sample, the frequency scores (α = .93) and stress appraisal scores (α = .94) demonstrated good internal consistency. Confirmatory factor analyses supported a multidimensional four-factor model that had an acceptable-to-good model fit (Lewis & Neville, 2015); however, several published studies also utilized a total mean score (Lewis et al, 2017; Moody & Lewis, 2019; M. G. Williams & Lewis, 2019).…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Based on the current sample, the frequency scores (α = .93) and stress appraisal scores (α = .94) demonstrated good internal consistency. Confirmatory factor analyses supported a multidimensional four-factor model that had an acceptable-to-good model fit (Lewis & Neville, 2015); however, several published studies also utilized a total mean score (Lewis et al, 2017; Moody & Lewis, 2019; M. G. Williams & Lewis, 2019).…”
Section: Methodsmentioning
confidence: 90%
“…Lewis et al (2017) have extended the biopsychosocial model of perceived racism (Clark et al, 1999) to gendered racism to investigate the link between gendered racial microaggressions and mental health outcomes. Quantitative research has found that greater experiences of gendered racial microaggressions are significantly related to greater psychological distress, symptoms of depression, traumatic stress, and poorer mental and physical health outcomes (Lewis et al, 2017; Lewis & Neville, 2015; Moody & Lewis, 2019; M. G. Williams & Lewis, 2019).…”
Section: Gendered Racism and Mental Healthmentioning
confidence: 99%
“…Our study was rooted in intersectionality theory, which argues that women who hold multiple minority social positions (i.e., gender, race, and sexual orientation) experience unique oppression and discrimination due to their interlocking social positions as Black and sexual minority ( Crenshaw, 1989 ). For Black women and Black SMW, experiencing intersectional oppression is linked with poor mental and physical health ( Agénor et al, 2014 , 2019 ; Kim et al, 2017 ; Lewis et al, 2017 ; Moody & Lewis, 2019 ); however, these studies do not investigate how intersectional oppression—approximated by holding multiple, intersecting, marginalized social positions (i.e., multiple marginalization)—confers excess risk for resource loss, including food insecurity ( Link & Phelan, 1995 ; Phelan et al, 2010 ; Warnecke et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies that demonstrate an association between exposure to racial discrimination and negative mental health outcomes (11)(12)(13) the hypothesis was set out that young black female university students young-adults (15) . previous research studies carried out in the study area.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the racial differences in self-esteem, researchers point out the link between racial discrimination and traumatic symptoms in university students ( 11 - 13 ) . Although it is assumed that the self-esteem of black women is more compromised when compared to non-black women, given the multiple violence to which they are exposed due to racism ( 11 - 12 ) , no studies were found that were dedicated to comparing the levels of self-esteem among these populations to support such an assumption in the Brazilian context. On the other hand, international studies comparing the effects of ethnic-racial identity on self-esteem show that there is a higher level of self-esteem among young black women than in any other young female ethnic group ( 14 ) .…”
Section: Introductionmentioning
confidence: 99%